Congenital thrombotic thrombocytopenic purpura presenting in adulthood with recurrent cerebrovascular events. Issue 10 (3rd October 2019) - Tenison, Emma; Asif, Ashar; Sheridan, Mathew
Abstract : Congenital thrombotic thrombocytopenic purpura (cTTP) is a rare, life-threatening disease, characterised by episodes of microangiopathic haemolytic anaemia (MAHA), thrombocytopenia and small vessel thrombosis. We describe a case of cTTP first diagnosed at age 70 years in a female presenting with an acute ischaemic stroke and thrombocytopenia, in whom A Disintegrin And Metalloproteinase with a Thrombospondin type 1 Motif, member 13 (ADAMTS13) levels were <10%, suggestive of thrombotic thrombocytopaenic purpura (TTP). The patient underwent plasma exchange and started rituximab for presumed immune TTP; however, anti-ADAMTS13 antibody titres were negative on two occasions. This, together with a history of pregnancies complicated by presumed disseminated intravascular coagulation, and two previous episodes of sepsis with MAHA, prompted investigation for cTTP, which was confirmed by genetic testing. Despite treatment with infusions of solvent/detergent-treated, virus-inactivated fresh frozen plasma, she has re-presented with further neurological deficit, associated with new infarcts on imaging. cTTP has a varied phenotype which, as demonstrated in this case, can include large vessel occlusion.